1998
DOI: 10.1002/(sici)1097-4547(19980901)53:5<511::aid-jnr1>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Potassium currents and excitability in second‐order auditory and vestibular neurons

Abstract: Potassium channels are involved in the control of neuronal excitability by fixing the membrane potential, shaping the action potential, and setting firing rates. Recently, attention has been focused on identifying the factors influencing excitability in second-order auditory and vestibular neurons. Located in the brainstem, second-order auditory and vestibular neurons are sites for convergence of inputs from first-order auditory or vestibular ganglionic cells with other sensory systems and also motor areas. Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Generally, calcium-dependent potassium currents contribute to the repolarizing phase of the action potential and to control the repetitive discharge of spikes. The calcium-dependent potassium currents of the vestibular nuclear neurons are known to underlie the afterhyperpolarization of action potential (12,13). In the present study, the depth of afterhyperpolarization was decreased by nitric oxide liberating agents and L-arginine, which coincides with the results of Park and Jeong (5).…”
supporting
confidence: 91%
“…Generally, calcium-dependent potassium currents contribute to the repolarizing phase of the action potential and to control the repetitive discharge of spikes. The calcium-dependent potassium currents of the vestibular nuclear neurons are known to underlie the afterhyperpolarization of action potential (12,13). In the present study, the depth of afterhyperpolarization was decreased by nitric oxide liberating agents and L-arginine, which coincides with the results of Park and Jeong (5).…”
supporting
confidence: 91%
“…Increasing numbers of K channels in rat MVN neurons, unlike the ganglion neurons, can lead to more sustained spiking. In maturing chick tangential neurons, in contrast, Peusner et al (1998) observed downregulation of LV K ϩ currents and more sustained spike patterns, observations that are consistent with the role of LV channels in rat primary afferent neurons, but following the opposite developmental trend.…”
Section: Development Of Firing Patternssupporting
confidence: 76%
“…With similar findings, earlier works also divided vestibular neurons into these two categories (Serafin et al, 1991;Johnston et al, 1994;Him & Dutia, 2001;Beraneck et al, 2003). In vestibular neurons, the combination of electrophysiological and pharmacological studies has distinguished different potassium and calcium conductances shaping the falling and AHP phases of the action potential (reviewed in Darlington et al, 1995;Peusner et al, 1998;Straka et al, 2005). Whether such conductances are also underlying I A and I B Mns of the rat oculomotor nucleus is not known.…”
Section: Type I Mnsmentioning
confidence: 85%